Contract adjustments and public procurement: an analysis of the law and its application - Smith, Katie Louise (2017)
The focus of this study is on the public procurement law applicable where UK contracting authorities seek to adjust the provisions of existing contracts. This study aims firstly to identify the law applicable to contract adjustments and secondly to establish how that law is applied in practice. In order to achieve the first objective, chapter 2 of this study set out the substantive law applicable to contract adjustments (including that arising from the Treaty on the Functioning of the European Union , the Public Contracts Regulations 2006 and 2015, and case law) and chapters 3, 4, and 5 consider respectively the content of that law specifically in the cases of review clauses, adjustments upon operation of law, and other adjustments. The second objective is met through considering the findings of relevant case law and also through undertaking empirical research. Chapter 6 set out the empirical research method, which focuses on adjustments to public private partnership contracts in the health, secure accommodation and education sectors. Data was collected through semi-structured questionnaires from private practice lawyers who advise contracting authorities on adjustments to those contracts within the scope of this research and contracting authorities themselves. Chapter 7 then sets out the findings of that empirical research. In the concluding chapter 8 the findings of the research are set out including an explanation of the ambiguities identified in the existing legal framework, and an articulation of the overall approach taken by contracting authorities when adjusting contracts, which suggests that a pragmatic approach (including assessment of likelihood of successful procurement law challenge) is taken to best enable the attainment of the contracting authorities’ procurement objectives. The study closes by setting out ways in which the law on contract adjustments could be clarified or improved.